Analysis Of Communication And Hr Implementation Of The Covid-19 Vaccination Program In The Elderly In North Musi Rawas District - Titien Kesuma; Haerawati Idris; Rostika Flora (Institute of Computer Science (IOCS), 2022)
The study, titled